2009
DOI: 10.11646/zootaxa.2198.1.2
|View full text |Cite
|
Sign up to set email alerts
|

Lethenteron ninae, a new nonparasitic lamprey species from the north-eastern Black Sea basin (Petromyzontiformes: Petromyzontidae)

Abstract: Lethenteron ninae sp. n., a nonparasitic lamprey, is described from rivers of western Transcaucasia in Russia and Abkhazia. It is distinguished from the other species of Lampetrinae in Europe and west Asia (Black Sea basin) by the combination of the following character states: adults with a dark blotch near the apex of the second dorsal fin; exolaterals absent; posterials either absent or more commonly present in a single incomplete row of 3-7 teeth (a toothless gap in the middle); transverse lingual lamina wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 20 publications
(5 citation statements)
references
References 9 publications
0
5
0
Order By: Relevance
“…probably due to the fact that this character, despite being broadly used in the taxonomy of lampreys (e.g. Naseka et al, 2009;Reid et al, 2011), may be influenced by ecological factors (e.g. latitude and temperature during the first stages of the larval development, references above), and should therefore be cautiously used in lamprey taxonomy.…”
Section: Morphological Differentiationmentioning
confidence: 99%
“…probably due to the fact that this character, despite being broadly used in the taxonomy of lampreys (e.g. Naseka et al, 2009;Reid et al, 2011), may be influenced by ecological factors (e.g. latitude and temperature during the first stages of the larval development, references above), and should therefore be cautiously used in lamprey taxonomy.…”
Section: Morphological Differentiationmentioning
confidence: 99%
“…dentition, relative size of the eye and oral disc) are limited to adult specimens (Hubbs & Potter, 1971). There is a particular lack of taxonomically informative morphological characters in brook lampreys, a collective term used to describe the non‐parasitic lampreys that occur within seven of the 10 recognized lamprey genera and that constitute more than half of the 41 described species (Renaud, 1997; Potter & Gill, 2003; Holčík & Šorić, 2004; Naseka et al , 2009; Renaud & Economidis, 2010). All lampreys spend c. 3–7 years as blind, filter‐feeding larvae in the silt bottoms of rivers and streams.…”
Section: Introductionmentioning
confidence: 99%
“…7b in Vladykov (1950) depicting the tail region of Lethenteron appendix (reported as Entosphenus lamottenii ) and in Fig. 2 in Naseka et al (2009) depicting the tail region of Lethenteron ninae . Additionally, Renaud et al (in press) found the same pigmentation pattern in ammocoetes of Lethenteron alaskense and Lethenteron camtschaticum .…”
Section: Discussionmentioning
confidence: 99%